Dorothea von Stetten-Kunstpreis : Dokumentation 1984 bis 1996. - Kunstmuseum Bonn; Dieckmann, Bärbel; Gronert, Stefan; Ronte, Dieter; Schrenk, Klaus (Bonn : Kunstmuseum Bonn, 1998)
Albers, Josef ; Breuer, Léo ; Brüning, Peter ; Calder, Alexander ; Calderara, Antonio ; Chillida, Eduardo ; Droese, Felix ; Fritsch, Lutz ; Garbert, Bernhard ; Hangen, Heijo ; Haypeter, Werner ; Heé, Barbara ; Hitzler, Franz ; Höckelmann, Antonius ; Hockney, David ; Hüppi, Alfonso ; Jakubaschke, Sigrun ; Kettel, Joachim ; Kiefer, Anselm ; Kirkeby, Per ; Kliemann, Carl-Heinz ; Mields, Rune ; Nevelson, Louise ; Noel, Martin ; Palermo, Blinky ; Poliakoff, Serge ; Poirier, Anne & Patrick ; Polke, Sigmar ; Rainer, Arnulf ; Rave, Horst ; Schneider, Gregor ; Schoofs, Rudolf ; Schultze, Bernard ; Stöhrer, Walter ; Tuttle, Richard ; Twombly, Cy ; Ursula ; Wesely, Michael ; Wu, Guang Yao ; Kiecol, Hubert ; Song, Hyun-Sook ; Witlatschil, Michael ; Bruch, Klaus vom ; Drössler, Graziella ; Kern, Stephan ; Stih, Renata ; Balkenhol, Stephan ; Dittrich, Andreas ; Fischer, Jochen ; Kummer, Raimund ; Oppermann, Manfred ; Erfurt, Stephan ; Pitz, Hermann ; Ruff, Thomas ; Wolff, Carl Emanuel ; Huber, Felix Stephan ; Mück, Steffen ; Sander, Karin ; Strik, Berend ; Florschuetz, Thomas ; Knöfel, York der ; Sonneville, Alain ; Unruh, Stefanie ; Werres, Birgit ; Axpe, Ana ; Herold, Jörg ; Schneider, Gregor ; Schwenk, Martin ; Wu, Guang Yao
Dorothea von Stetten-Kunstpreis : Dokumentation : 1984 bis 1996, Kunstmuseum Bonn, März 1998
Duits
boek